KETENTUAN PAJAK KONSUMEN PERSPEKTIF MAQASHIDUSH SYARIAH DAN UNDANG-UNDANG PAJAK PERTAMBAHAN NILAI (PPN) NO. 8 TAHUN 1983 (TENTANG PAJAK PERTAMBAHAN NILAI BARANG) - Mustofa; Siti Romlah (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
Maqashid sharia there is "illah". Allah can be said to be the same as maqashid. Illah is also used in qiyas to issue a law. According to al-Syatibi, al-illah means wisdom (wisdom) and mashalih (maslahat-maslahat) relating to orders (awamir) and permissibility (ibahah) and mafasid relating to prohibitions (nawahi). So, the difficulty (masyaqqah) is god in requiring the qasar to pray. So, Allah is maslahah. The scope of maqashid sharia includes justice, equality, simplicity, and does not exceed limits, facilitates and relieves, brings goodness and stays away from harm or damage, unity and agreement as well as maintaining human life and improving it towards goodness which includes aspects of thinking or reason, work and relationships with others. man. Imam al Juwaini termed maqashid sharia as "Jalbu Wa Dar'u" attracting or getting something that has not happened and keeping something that has happened, namely determining what is good and rejecting harm. Imam al Juwaini divides mashlahah into three levels, namely Dlaruriyah, Hajiyah, and Tahsiniyah. Dlaruriyah is a need at the primary level. If this need is not met, it will be fatal to the human soul, such as the need for rice as a staple food. If basic food is not met, it will starve and if it gets worse it will cause death. So this level of needs ranks first to be met, including clothing, food, and shelter. The birth of the National Tax Law, as a replacement for the previously applicable tax laws whose contents mostly originate from the Dutch East Indies era, such as the Corporate Tax Ordinance of 1925, the Wealth Tax Ordinance of 1932 and the Income Tax Ordinance of 1944. This is one of the factors that support the success of development that has been carried out until now, so that its birth has historical meaning for the nation and state. Key word : , ,